Nero : a novel - Iggulden, Conn (Pegasus Books, 2024)
The story begins with a hand curled around another man's throat. This is Roman justice: Emperor Tiberius first dispatches a traitor--a friend he once trusted with the city--then the man's whole family and all of his friends. It is as if he never existed. Into this fevered forum, a child is born. His mother is Agrippina, granddaughter of Emperor Augustus. But their imperial blood is neither balm nor protection. Rather, it is a liability. Blood is easily spilled or poisoned. So swiftly corrupted. As the aging, paranoid Tiberius becomes blind to the ignoble end awaiting him, Agrippina sees the future. Her once-exiled brother Caligula is next in succession, which brings her another step closer to the heart of the empire--to power, ambition, and danger. Every day she will face soldiers, senators, rivals, silver-tongued pretenders, each vying for position. One mistake risks exile, incarceration, execution. Or, worst of all, perhaps the loss of her infant son. Because Agrippina knows that, even in your darkest moments, opportunity rises. Her son is everything. She can make this boy, shape him into Rome itself--the man before whom all must kneel. But first, Agrippina and Nero must survive... --